Studi Korelasi dan Regresi Antara Jumlah Pakan Terhadap Produksi Ikan Bandeng di Desa Kendalkemlagi Kecamatan Karanggeneng Kabupaten Lamongan - Sa'adah, Wachidatus (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Milkfish (Chanos chanos) is a fishery product that is one of the leading commodities in Lamongan Regency, and ranks fourth in its production in East Java after Sumenep, Gresik and Sidoarjo Regencies. This study examines the correlation and regression studies between the amount of feed and milkfish production in Kendalkemlagi Village, with the hope that it can be a basis for supporting the sustainability of milkfish cultivation and improving the welfare of farmers through increasing optimal production results. This study is a quantitative study with a purposive sample method in selecting its samples, and the calculation analysis used is correlation and regression analysis. The results of the study obtained a correlation value of 0.994 indicating a very strong and positive relationship between variable X (amount of feed) and variable Y (milkfish production), meaning that the more feed given, the higher the milkfish production. With a t-count value of 18.17 which is much greater than the t-table of 2.776 (df = 4, ɑ = 0.05, two-way), then H0 is rejected, this means that the relationship between the amount of feed and milkfish production is significant. Then, from the linear regression equation Y = −191.33+0.71x, it means that an increase in the amount of feed will be followed by a proportional increase in milkfish production, so that there is an influence between the two.